2002
DOI: 10.1093/clinchem/48.8.1296
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Bioinformatics Approaches for Identification of Serum Biomarkers to Detect Breast Cancer

Abstract: Background: Surface-enhanced laser desorption/ionization (SELDI) is an affinity-based mass spectrometric method in which proteins of interest are selectively adsorbed to a chemically modified surface on a biochip, whereas impurities are removed by washing with buffer. This technology allows sensitive and high-throughput protein profiling of complex biological specimens. Methods: We screened for potential tumor biomarkers in 169 serum samples, including samples from a cancer group of 103 breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
274
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 811 publications
(286 citation statements)
references
References 12 publications
7
274
0
5
Order By: Relevance
“…After normalizing the MS signals by either total ion current and/or total peak intensity, the intensity values of the protein/ peptide peaks is highly reproducible. The intra-assay and inter-assay CVs for the normalized intensities of majority of the SELDI peaks are between 5% and 25% [103,104]. With the use of standardized experimental protocol and quality control strategy, the inter-laboratory CVs of the normalized peak intensities are between 15% and 36% [105].…”
Section: Quantitative Issues In the Seldi-tof Mass Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…After normalizing the MS signals by either total ion current and/or total peak intensity, the intensity values of the protein/ peptide peaks is highly reproducible. The intra-assay and inter-assay CVs for the normalized intensities of majority of the SELDI peaks are between 5% and 25% [103,104]. With the use of standardized experimental protocol and quality control strategy, the inter-laboratory CVs of the normalized peak intensities are between 15% and 36% [105].…”
Section: Quantitative Issues In the Seldi-tof Mass Spectramentioning
confidence: 99%
“…As of today, there are at least 850 publications on applications of SELDI-TOF MS to protein biomarker discovery. It has been used to analyze a wide range of biological samples, for example, serum [100,[103][104][105][106], plasma [110,113,115], urine [101,113,116], tears [117][118][119], cerebrospinal fluid [120][121][122], amniotic fluid [123][124][125], tissue/cell lysate [107,[126][127][128], etc. It has been applied to the discovery of potential biomarkers for various types of diseases, for example, cancers [103-106, 112, 129], infectious diseases [99,100,115,130], autoimmune diseases [118,131], eye diseases [117,119], neurological diseases [120][121][122], perinatal and neonatal diseases [123][124][125][126], etc.…”
Section: High-throughput Technology For Biomarker Discoverymentioning
confidence: 99%
“…In recent years proteomic characterization of biological samples has been successfully applied to identify potential diagnostic or prognostic markers to detect and monitor the onset, prognosis and progress of a disease state. [14][15][16] This led us to hypothesize that wound fluid produced during venous ulceration could provide a means of acquiring information regarding failed or prolonged healing of chronic ulcers. 17 Furthermore, collection of CWF is relatively easy and noninvasive, and CWF contains a heterogeneous mixture of proteins or peptides that might be indicative of the healing status of the wound environment.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the SELDI technology discovered a panel of three biomarkers to separate stage 0-I breast cancer patients from noncancer controls. Bootstrap cross-validation demonstrated that a sensitivity of 93 % for cancer patients and a specificity of 91 % for controls were achieved [6] . The SELDI-TOF MS was also adopted to discover differential biomarkers for lung cancer serum, and the results have been filed in the Patent Corporation Treaty by our group.…”
Section: Research Progress and Applicationsmentioning
confidence: 99%